Story found or story lost? Storytelling in audiovisual municipality branding - Moldenæs, Turid (Scandinavian Journal of Public Administration, 2016)
The aim of the article is to add to our knowledge of reputation management efforts in municipalities. Despite the multitude of such efforts, few have been studied. The specific focus is on the contents of reputation films made by Norwegian municipalities. Is there a story in these films? If so, what is the message conveyed, and is it convincing in its attempt to present the different municipalities as unique? The analysis shows that the films lack a story, and as such they are not suitable to capture the attention of an audience, be remembered and retold. It also shows that, despite the fact that municipalities vary in size, are located in different parts of the country, have different key industries and varying topographies, traditions and histories, they struggle to convey their differences. The municipality film seems to have developed into a romanticising genre, offering little authentic representation of the specific municipality presented, life in small places as well as life in general. Thus, it may also be difficult for those who live there to identify with the message.